Pengaruh Kepemimpinan Otentik Terhadap Perilaku Kewargaan Organisasional - Rizkita Cahya Henviana; Mamun Sutisna (Jurnal Riset Bisnis dan Investasi, 2017)
This study aims to determine the role of Authentic Leadership (AL) and Organizational Citizenship Behavior (OCB) also to analyze the relationship of these variables in Hypermart Bandung. This study consists of 4 dimension of AL (self awareness, relational transparency, internalized moral perspective, and balance processing) and 5 dimensions of OCB (altruism, civic virtue, conscientiousness, courtesy and sportsmanship). Research using linear regression and descriptive statistics. Data collection used questionnaire given to 150 employees of Hypermart Bandung. The results of this study indicate that the role of AL of the leader in Hypermart resulted in good category. Similarly, OCB on employees resulted in good category. It is also known that AL has a positive and significant effect on OCB. The level of AL influence on OCB is 23.7%, while 76.3% is influenced by other factors not explained in this research.